Information content of equity analyst reports - Asquith, Paul; Mikhail, Michael B.; Au, Andrea S. (Journal of Financial Economics, 2005)
We catalog the complete contents of Institutional Investor All-American analyst reports and examine the market reaction to their release. Including the justifications supporting an analyst's opinion reduces, and in some models eliminates, the significance of earnings forecasts and recommendation revisions. Analysts both provide new information and interpret previously released information. The information in a report is most important for downgrades; target prices and the analyst's justifications are the only significant elements for reiterations. No correlation exists between valuation methodology and either analyst accuracy or the market's reaction to a report. Our adjusted R2s are much larger than those of studies using only summary measures.